Winter's tail : how one little dolphin learned to swim again - Hatkoff, Juliana (Scholastic Press, 2009)
Describes the rescue and rehabilitation of a young Atlantic bottlenose dolphin, named Winter, who received an artificial tail after being badly injured when caught in a crab trap.